In vivo and in vitro degradation of peptide YY3-36 to inactive peptide YY3-34 in humans - Toräng, Signe; Bojsen-Møller, Kirstine Nyvold; Svane, Maria Saur; Hartmann, Bolette; Rosenkilde, Mette Marie; Madsbad, Sten; Holst, Jens Juul (American journal of physiology. Regulatory, integrative and comparative physiology, 2016)
Peptide YY (PYY) is a 36-amino-acid peptide released from enteroendocrine cells upon food intake. The NH2 terminally truncated metabolite, PYY3-36, exerts anorexic effects and has received considerable attention as a possible antiobesity drug target. The kinetics and degradation products of PYY metabolism are not well described. A related peptide, neuropeptide Y, may be degraded from the COOH terminus, and in vivo studies in pigs revealed significant COOH-terminal degradation of PYY. We therefore investigated PYY metabolism in vitro after incubation in human blood and plasma and in vivo after infusion of PYY1-36 and PYY3-36 in eight young, healthy men. A metabolite, corresponding to PYY3-34, was formed after incubation in plasma and blood and during the infusion of PYY. PYY3-34 exhibited no agonistic or antagonistic effects on the Y2 receptor. PYY1-36 infused with and without coadministration of sitagliptin was eliminated with half-lives of 10.1 ± 0.5 and 9.4 ± 0.8 min (means ± SE) and metabolic clearance rates of 15.7 ± 1.5 and 14.1 ± 1.1 ml·kg(-1)·min(-1) after infusion, whereas PYY3-36 was eliminated with a significantly longer half-life of 14.9 ± 1.3 min and a metabolic clearance rate of 9.4 ± 0.6 ml·kg(-1)·min(-1) We conclude that, upon intravenous infusion in healthy men, PYY is inactivated by cleavage of the two COOH-terminal amino acids. In healthy men, PYY3-36 has a longer half-life than PYY1-36.